Cutaneous silent periods in the assessment of mild cervical spondylotic myelopathy - Stetkarova, Ivana; Kofler, Markus (Spine, 2009)
STUDY DESIGN: Clinical, neuroradiologic, and neurophysiologic description of 21 patients with compressive cervical spondylotic myelopathy (CCSM). OBJECTIVE: To describe the utility of cutaneous silent periods (CSPs) for functional evaluation of mild CCSM. SUMMARY OF BACKGROUND DATA: Electroneurography, electromyography, and somatosensory and motor evoked potentials (SEPs, MEPs) are routinely used for comprehensive functional neurophysiological evaluation of CCSM. CSPs have been reported in various intramedullary spinal cord lesions, however, they have not been systematically studied in mild CCSM. METHODS: We investigated 21 patients with multilevel CCSM as documented by magnetic resonance imaging. We recorded CSPs in thenar muscles after noxious digit II stimulation and compared them with median and tibial nerve SEPs and MEPs obtained from abductor digiti minimi and tibialis anterior muscles. Electroneurography and electromyography were obtained in affected myotomes. RESULTS: CSP onset and end latencies were delayed, and CSP duration was shortened, in CCSM patients. CSP abnormalities were present in 17 patients of whom all, but 1 presented with intramedullary magnetic resonance imaging hyperintensity. All 11 limbs affected by hypalgesia and thermhypesthesia had abnormal CSPs, whereas no spinothalamic deficit was noted in any limb with normal CSPs. CSP onset latency was inversely correlated with JOA score and N13 amplitude, and was positively correlated with central motor conduction time to abductor digiti minimi. CSP duration was inversely correlated with central motor conduction time to tibialis anterior. Electromyographic abnormalities were found in 7 patients. CONCLUSION: We confirm the value of neurophysiological evaluation of CCSM. MEPs were more frequently abnormal than SEPs. CSP abnormalities were almost equally sensitive as upper limb MEPs, and were highly associated with spinothalamic dysfunction. The high correlation of CSP abnormalities with corticospinal tract dysfunction suggests supraspinal influence on CSPs. Our findings corroborate the utility of CSP testing in the comprehensive assessment of intramedullary spinal cord dysfunction in CCSM.
Keywords: dospělí; kosterní svaly; Nervous System Physiological Phenomena; Female; Adult; ženské pohlaví; nervový systém - fyziologické jevy; nervus tibialis; Spondylosis; somatosenzorické evokované potenciály; lidé; Evoked Potentials, Somatosensory; Neural Conduction; elektromyografie; studie případů a kontrol; spinální stenóza; krční obratle; Muscle, Skeletal; motorické evokované potenciály; nervové vedení; Median Nerve; Electromyography; Evoked Potentials, Motor; Male; spondylóza; Aged; Case-Control Studies; Tibial Nerve; Spinal Cord Diseases; Spinal Stenosis; lidé středního věku; nemoci míchy; Cervical Vertebrae; senioři; mužské pohlaví; Middle Aged; nervus medianus; Humans